Outcome of shaft fractures among children treated with elastic stable intramedullary nailing - Ahmad, Mahmood; Tahir, Tahir El; Ahmad, Saba; Ahmad, Umair (International Journal of Research in Medical Sciences, 2020)
Background: Long bone fractures are frequent occurrence among children and considered a frequent pediatric orthopedic injury requiring hospitalization. Authors aimed to retrospectively analyze the outcome of fixation of long bone fractures with elastic stable intramedullary nailing (ESIN) among children and adolescents. Methods: From 2010 to 2018, ESIN was performed on 128 children aged 2 to 17 years having single shaft fractures of long bones. The data related to associated injuries, postoperative complications, postoperative treatment, till bony union or removal of rods, mal-union, functional deficit, need for secondary surgical intervention and subjective complaints at follow-up originated from postoperative clinical and radiological consultations carried out regularly. The primary end points were time of complete radiological union or removal of rods. Results: The mean age at the time of accident was 9.5 years. There were 37 (28.9%) femoral fractures, 16 (12.5%) of the lower leg, 51 (39.8%) fractures of radius/ulna and 24 (18.8%) of the humerus. In 2 (2.3%) children, reoperation was necessary due to prominent ends of elastic rods and 6 (4.7%) had early removal of rods due to same reasons. End point of the study, removal of rods noted in 126 (82.8%), radiological evidence of union in 7 (5.5%) and 15 (11.7%) cases were lost at follow-up. Conclusions: ESIN fixation of diaphyseal fractures in children and adolescents is safe. ESIN was found to be minimally invasive method, noted to produce excellent functional as well as cosmetic outcomes.